The Proper Implementation of Technology into the English Language Arts Classroom: TECHNOLOGY IN THE ELA CLASSROOM - Dewire, Abigail (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2021)
Prior to 2020, technology was slowly being integrated into the classroom. Technology integration is expensive and because of this, schools with more funding were making the leap at more rapid rates than schools with less funding. In 2020, the Covid-19 pandemic hit and there was a heavy push for schools across the country to get laptops into the hands of every student. This pandemic gave students who previously did not have access to internet the opportunity to learn in a 1:1 laptop setting. With laptops in the hands of every student, kids are spending more time than ever before in front of screens. Now that every student has access to the technology, educators need to explore the dangers associated with its overuse and establish boundaries to create the most optimal learning environment.